Fine scale measurements in Belgian coastal sediments reveal different mobilization mechanisms for cationic trace metals and oxyanions. (December 2020) - Zhou, Chunyang; Gaulier, Camille; Luo, Mingyue; Guo, Wei; Baeyens, Willy; Gao, Yue
Graphic abstract: Highlights: Fine scale measurements in BCZ sediments reveal 2 mobilization mechanisms. Fe plays a dominant role in both mobilization mechanisms in BCZ sediments. Acidification in anoxic sediment causes cationic metal mobilization. Fe-oxide dissolution controls oxyanion's mobilization in sub-oxic sediment. Metal/Fe ratios in FeS are constant with an abundance sequence Ni > Cu > Pb > Co. Abstract: Belgian coastal sediment serves as an important sink for trace elements, yet a systematic study covering a wide range of elements including redox-sensitive metals (Fe, Mn, and Co), cationic trace metals (Cd, Pb, Ni, Cu, and Zn), oxyanions (P, V, As, and Mo), and sulfide has not been performed and the mechanisms controlling their mobilization were not investigated. Here, a passive sampling technique, Diffusive Gradients in Thin-films (DGT), was used in situ to obtain high resolution concentration profiles of these elements in the sediment porewater. Our results revealed two mobilization mechanisms of cationic trace metals and oxyanions in Belgian coastal sediments, both strongly linked to the cycling of Fe. Mobilization of Co, Pb, Ni, and Cu is controlled by electrogenic sulfur oxidation, acidification of the porewater and dissolution of FeS, while that of oxyanions (P, V, and As) is controlled by reductive dissolution of Fe oxyhydroxides. Constant cationic trace metal to Fe molar ratios were established in FeS, while the oxyanion to Fe ratios in Fe oxyhydroxides differ significantly between sampling stations, which is primarily caused by competing effects. We found no evidence that cationic trace metal mobilization was related to Fe oxyhydroxides, or oxyanion mobilization to FeS. This suggests that particulate organic matter forms the major pathway for cationic trace metal input in coastal sediments and that oxyanions will not be incorporated in FeS but form their own oxyanion-sulfide compound. These findings will contribute to a better understanding of the mobilization mechanisms of cationic trace metals and oxyanions in coastal sediments, and of their biogeochemical cycling in coastal ecosystems.